Blockchain basics a non-technical introduction in 25 steps - Drescher, Daniel (Apress, 2017)
In 25 concise steps, you will learn the basics of blockchain technology. No mathematical formulas, program code, or computer science jargon are used. No previous knowledge in computer science, mathematics, programming, or cryptography is required. Terminology is explained through pictures, analogies, and metaphors. This book bridges the gap that exists between purely technical books about the blockchain and purely business-focused books. It does so by explaining both the technical concepts that make up the blockchain and their role in business-relevant applications.
Includes bibliographical references and index. - Vendor-supplied metadata
Keywords: Electronic funds transfers; Blockchains (Databases); Database management; Electronic commerce; Data encryption (Computer science); Computer Science; Database Management; Data Encryption; Special Purpose and Application-Based Systems; Data Storage Representation; Banking; Capital Markets; Transferts électroniques de fonds; Chaînes de blocs; Bases de données; Gestion; Commerce électronique; Chiffrement (Informatique); Data encryption; Expert systems / knowledge-based systems; Data mining; Finance; Databases; BUSINESS & ECONOMICS; Banks & Banking; BUSINESS & ECONOMICS; E-Commerce; General; COMPUTERS; Databases; General